19=-4(h+5)+h

Simple and best practice solution for 19=-4(h+5)+h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19=-4(h+5)+h equation:


Simplifying
19 = -4(h + 5) + h

Reorder the terms:
19 = -4(5 + h) + h
19 = (5 * -4 + h * -4) + h
19 = (-20 + -4h) + h

Combine like terms: -4h + h = -3h
19 = -20 + -3h

Solving
19 = -20 + -3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '3h' to each side of the equation.
19 + 3h = -20 + -3h + 3h

Combine like terms: -3h + 3h = 0
19 + 3h = -20 + 0
19 + 3h = -20

Add '-19' to each side of the equation.
19 + -19 + 3h = -20 + -19

Combine like terms: 19 + -19 = 0
0 + 3h = -20 + -19
3h = -20 + -19

Combine like terms: -20 + -19 = -39
3h = -39

Divide each side by '3'.
h = -13

Simplifying
h = -13

See similar equations:

| x+3-2x+5=10 | | 2x-2=5x-12 | | 4w^2=4w+3 | | 7x-3x=45-4x | | 35=(2x+3)*x | | 6x+5=4x-4 | | 2*1/3+2/1/3=x | | 4x-2x-2=2x | | -(8x-1)+x=-6x+6(x+6) | | x+2=-2x^2 | | 18x^3y-6x^7y=0 | | 2.3w-3.2+4.1=-6 | | 6x+14=29 | | 9t^2+2=9t | | 6x^2-21x-45=0 | | 7c^2-2c=1 | | 25x^3+5x^2-10x-2=0 | | m^2-14m+49=0 | | x^2+16x+53= | | -14=8-3a | | x^2+20x-18=0 | | -z^2+6=-5z | | m+2m+(m+10)=180 | | 7x^2-x-1=0 | | 4x-x+4=2x-6+14 | | .3k^2-6k=2.4 | | 1005=0.005x+0.95 | | 3(c+1/3)=4 | | 2_3a=16 | | 12=4-2x | | 6=-3x(x+4) | | 5=7-2x |

Equations solver categories